Original papersSurgical treatment of rhinophyma - Lewandowicz, Edward; Witmanowski, Henryk; Sobieszek, Daria (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2009)
Introduction: Rhinophyma is the end-stage of rosacea. It is a slow, progressive, gentle process which leads to deformation and functional disturbances of the nose. Hyperplasia and hypertrophy of perifollicular sebaceous glands, fibrous tissue proliferation and vessel dilatation (telangiectasias) are observed. Histopathological examination shows inflammation and hyperkeratosis of pilosebaceous units, fibrous tissue proliferation, collagen hyperplasia, vasodilatation and oedema. Similar changes in the histopathological picture are observed in the case of elephantiasis. Treatment of rhinophyma is usually limited to avoiding stimulating factors, proper cleaning and treatment of secondary infections and inflammation. There have been many studies on treatment with vitamins, hormones, fibrinolytic factors, silver nitrate, UV waves, x-rays and radium. Surgical treatment still remains the basic method of treatment of rhinophyma. Material and methods: From 1972 to 2008 in the Clinic of Plastic, Reconstructive and Aesthetic Surgery of the University of Medical Sciences in Łódź, 32 cases of rhinophyma were treated. In 28 cases the treatment involved simple cutting of the lesion with a scalpel with complementary electrocoagulation, and in 4 cases complete excision of the changed tissues with simultaneous covering of the wound with a skin graft. Results: Good results were obtained in 21 patients, satisfactory in 10, and bad in 1 case. Conclusion: The long-term observations have proved satisfactory cosmetic and functional results.